Effects of the Wrist Band Acupressure Technique on the Severity of Nausea among Patients Receiving Highly Versus Moderately Emetogenic Chemotherapy - Zahraa Jasim Alwan; Hassan Abdullah Athbi (Kufa Journal for Nursing Sciences)
Background: Chemotherapy is an important therapeutic option for patients with cancers, but it is also associated with a number of adverse effects that can affect practically every body system. The most frequent side effects of chemotherapy are gastrointestinal in nature, such as nausea and vomiting. The pericardium 6 (P6) is one of the most important points used in acupressure techniques for treating nausea and vomiting.